Working with culture psychotherapeutic interventions with ethnic minority children and adolescents (The Jossey-Bass social and behavioral science series, 1992)
"Ethnic minority children and adolescents often face unique challenges in their development and in their adjustment to mainstream society. Mental health providers must develop approaches that are sensitive to the special needs of this growing population. Working with Culture presents culturally responsive psychotherapeutic interventions for specific problems commonly experienced by ethnic minority youth." "Each chapter of Working with Culture offers case examples, along with a strong clinical how-to approach for dealing with problems such as cross-racial foster care, gang involvement, child abuse, and substance abuse. From showing how racial socialization can be used as a tool in treating African American children to describing how play therapy can help in the exploration of cultural issues with Hispanic American children, the authors provide an in-depth look at the more practical aspects of treating ethnic minority youth."--BOOK JACKET.